Knowledge structure and dynamic evolution of nanomedicine in liver cancer research: a scientometric analysis and visualization - Li, Shaodong; Cui, Dapeng; Shao, Bo; Kang, Zhenhua; Yan, Guoqiang (Frontiers in Pharmacology, 2025)
BackgroundNanomedicine has received much attention for its potential applications in the diagnosis and treatment of liver cancer. However, no bibliometric evaluation has been conducted to present an assessment of scientific progress in the field. The aim of this study is to comprehensively catalog the cooperation and influence of journals, countries, institutions, and authors in the field of nanomedicine in liver cancer from the perspective of bibliometrics, evaluate the clustering evolution of knowledge structure, and uncover hot topics and emerging themes.MethodsArticles and reviews related to nanomedicine and liver cancer were retrieved from the Web of Science Core Literature Library using Topic Search. #1 T= (“Hepatic Neoplasm*” OR “Liver Neoplasm” OR “Liver Cancer*” OR “Hepatocellular Cancer*” OR “Hepatic Cancer*“), #2 T= “nano*“, the search strategy is set as #1 AND #2 limited to Science Citation Index Expanded database source, with no limitation of publication types and language/time. Bibliometric studies were conducted using CiteSpace and VOSviewer.Results2,648 articles and reviews were included from 2000 to 2024. The number of articles regarding nanomedicine in liver cancer showed an increasing trend. Analysis of the most productive journals shows that most are specialized in nanoscience and nanotechnology, pharmacology and pharmacy, and chemistry and multidisciplinary. These publications mainly come from 8,782 institutions in 297 countries led by China and the United States of America. Shao D published the most papers among the publications, while Jemal A had the most co-citations. The macroscopical sketch and micro-representation of the whole knowledge field are realized through co-citation analysis. Hepatocellular carcinoma, targeted delivery, sorafenib nanoparticles, and others are current and developing areas of study. The keywords “nanocrystals,” “biodistribution,” and “particles” also may be the focus of new trends and future research.ConclusionIn this study, bibliometrics and visual methods were used to review the research of nanomedicine in liver cancer comprehensively. The article will help scholars to gain a better understanding of the dynamic evolution of nanomedicine applications in liver cancer and point the directions for future research.